Pengaruh Penggunaan Akun Instagram @infodenpasar Terhadap Pemenuhan Kebutuhan Informasi Anak Muda Di Kota Denpasar - Dewi, Kadek Ayu Shintya; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
@infodenpasar is an information-based Instagram account that provides various information and the latest news related to Denpasar, Bali and Indonesia. This account makes it easier for the Balinese to carry out their activities by presenting accurate information and avoiding hoax news. The goals of this study is to see the influence of using the Instagram account @infodenpasar has on meeting the information needs of young people in Denpasar City. Theories used include new media theory, uses and effects, social media, Instagram, and information needs. This research used explanatory quantitative research method. The researcher was distributing questionnaires to 80 respondents who were determined through nonprobability sampling and purposive sampling techniques. To analyze the data findings, this research used a simple linear regression statistical test using SPSS 26. The results showed that there was an effect of social media usage on the information needs variable, with a coefficient of determination (R Square) of 0.542. According to the results, fulfillment of the information needs of young people in Denpasar City is 54.2% influenced by the use of the Instagram account @infodenpasar. This means that the use of the Instagram @infodenpasar social media account has a significant effect on fulfilling the information needs of young people in Denpasar City. Keywords: Social Media, Instagram account @infodenpasar, Information Needs